2017
DOI: 10.1021/acs.energyfuels.7b02228
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Effects of Supercritical Carbon Dioxide Extraction on Physicochemical Characteristics of Chinese Low-Rank Coals

Abstract: The effects of supercritical carbon dioxide (SCCO2) extraction on coal composition, coal rank, pore structure, and combustion reactivity of three typical Chinese low-rank coals (LRCs) were investigated in this study. The results show that the SCCO2 extraction process has significantly reduced the moisture content and increased the fixed carbon content of LRCs. The oxygen/carbon atomic ratio of upgraded LRCs decreases, indicating that the coal rank of upgraded LRCs improves after SCCO2 extraction, which is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…According to Wang et al [27], the decrease in surface functional group density may be attributable to the extracting effect or reactivity of ScCO2 fluid. The decrease of -OH groups may be related to the dissolution of ScCO2 to the inherent moisture in the coal samples; however, the elimination of the amide carbonyl groups may be related to the extraction of the organic volatile corresponds from coal with ScCO2 exposure, as demonstrated by Li et al [28]. In addition, a decrease in the distribution of mineral matter content in the coal samples was observed after ScCO2 exposure.…”
Section: Effect Of Scco 2 Exposure On Coal Surface Propertymentioning
confidence: 89%
“…According to Wang et al [27], the decrease in surface functional group density may be attributable to the extracting effect or reactivity of ScCO2 fluid. The decrease of -OH groups may be related to the dissolution of ScCO2 to the inherent moisture in the coal samples; however, the elimination of the amide carbonyl groups may be related to the extraction of the organic volatile corresponds from coal with ScCO2 exposure, as demonstrated by Li et al [28]. In addition, a decrease in the distribution of mineral matter content in the coal samples was observed after ScCO2 exposure.…”
Section: Effect Of Scco 2 Exposure On Coal Surface Propertymentioning
confidence: 89%
“…On the one hand, the interactions change the coal pore structure. Some studies have reported that scCO 2 decreased the micropore surface area and the volume of dry coals. Similar trends were also found in the meso- and macropores of dry bituminous coals. Conversely, the scCO 2 increased the meso- and macropore structure parameters of anthracites. , On the other hand, the interactions change the surface chemistry properties of coal. , scCO 2 could extract some polycyclic aromatic hydrocarbons and aliphatic hydrocarbons from the coal matrix. , Moreover, scCO 2 typically reduces the content of weak polar functional groups of coal, including lipids, epoxies, and hydrocarbons ,,,, and, finally, alters the ratio of aromatic carbon to alkyl carbon . The pore structure and surface chemistry properties are the two main factors affecting the adsorption, diffusion, and flow of fluids within coal reservoirs. ,, Aiming to better understand the practical CO 2 –ECBM, it is of great significance to further explore the influence of scCO 2 on the physicochemical properties of coal.…”
Section: Introductionmentioning
confidence: 99%
“…13,21−24 scCO 2 could extract some polycyclic aromatic hydrocarbons and aliphatic hydrocarbons from the coal matrix. 11,13 Moreover, scCO 2 typically reduces the content of weak polar functional groups of coal, including lipids, epoxies, and hydrocarbons 13,19,21,23,24 and, finally, alters the ratio of aromatic carbon to alkyl carbon. 22 The pore structure and surface chemistry properties are the two main factors affecting the adsorption, diffusion, and flow of fluids within coal reservoirs.…”
Section: Introductionmentioning
confidence: 99%